MEMBANGUN KINERJA MELALUI KEPUASAN KERJA : ANALISIS PENGARUH PELATIHAN DASAR, SUPERVISOR SUPPORT DAN LEARNING ORGANIZATION PADA CPNS BADAN PUSAT STATISTIK TAHUN 2025 - Geminda Prihatma Prasetya; Subur Karyatun (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to analyze the influence of Basic Training, Supervisor Support, and Learning Organization on Employee Performance, both directly and indirectly through Job Satisfaction as a mediating variable. The study used a quantitative approach with stratified random sampling as the sampling method and a survey of 249 Civil Servant Candidates (CPNS) from the Central Statistics Agency (BPS) across 34 provinces. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis. The results indicate that Basic Training, Supervisor Support, and Learning Organization have a positive and significant effect on CPNS Job Satisfaction. Basic Training also has a positive and significant effect on Employee Performance, while Learning Organization has a significant effect but with a small practical contribution. Supervisor Support does not have a significant direct effect on Employee Performance. Job Satisfaction has a positive and significant effect on Employee Performance and mediates the effect of Basic Training and Learning Organization on Employee Performance, but does not mediate the effect of Supervisor Support. The strong model explained 55.7% of the variation in Employee Performance and the moderate model explained 38.1% of the variation in Job Satisfaction. These findings indicate basic training as a key strategy in improving CPNS performance and emphasize the importance of strengthening the Learning Organization to boost CPNS job satisfaction. Practical implications emphasize the importance of strengthening Learning Organization practices and integrating supervisor support into the team leader performance appraisal system, as well as strengthening team leader competencies